Ethyl Ferulate Suppresses Esophageal Squamous Cell Carcinoma Tumor Growth Through Inhibiting the mTOR Signaling Pathway - Pang, Mengjun; Xie, Xiaomeng; Zhang, Yuanyuan; Laster, Kyle Vaughn; Liu, Kangdong; Kim, Dong Joon (Frontiers in Oncology, 2022)
Ethyl ferulate is a phenylpropanoid compound isolated from the medicinal herb Ferula. Although ethyl ferulate has anti-inflammatory, antioxidant, and neuroprotective activities with potential use in the nutraceutical and pharmaceutical industry, its anticancer effects and underlying molecular mechanisms against esophageal squamous cell carcinoma (ESCC) have not been investigated. This study investigates the anticancer activity and molecular mechanism of ethyl ferulate in ESCC. MTT, focus formation, soft agar, and cell cycle analysis were used to determine the effect of ethyl ferulate on cell proliferation and cell cycle. Potential candidate proteins were screened and verified via Western blotting, in vitro kinase assay, and in vitro pull-down assay. Mammalian target of rapamycin (mTOR) knockdown cell lines were established by lentiviral infection with shmTOR. The effect of ethyl ferulate on tumor growth was assessed using ESCC patient-derived xenograft models. Ethyl ferulate significantly inhibited cell growth and induced G1 phase cell cycle arrest in ESCC cells. Ethyl ferulate reduced the activity of mTOR in vitro. The inhibition of ESCC cell growth by ethyl ferulate is dependent on mTOR expression. In addition, ethyl ferulate strongly reduced ESCC patient-derived xenograft tumor growth in an in vivo mouse model. Ethyl ferulate is an mTOR inhibitor that can suppress ESCC progression and may be a novel candidate compound for esophageal cancer chemoprevention.